(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today’s world is fastly developing in terms of Finance, Economics, Business. So it requires Trained and suitable employees in their respective field. Production of such kind of personnel is duty of Business education institutes. So, Business education institute must adopt some best practices like Strategic Management and Planning. Strategic Management in Business education plays an important role for achieving objectives. Strategic Management is the identification of the purpose of the organization, plans and actions to achieve them. Strategic Management helps in assessing opportunities and threats, keeping in mind Strengths and Weaknesses. Where as Strategic Planning is the future oriented activity.